MP18: A patient focused information design intervention to support the mTBI Choosing Wisely recommendation. (15th May 2017) - Hair, H.; Boudreau, D.; Rice, C.; Grigat, D.; VandenBerg, S.D.; Ruhl, G.; Dowling, S.
Abstract : Introduction: Within Alberta, 30% of patients presenting to emergency with minor traumatic brain injury (mTBI) will receive a CT scan before being sent home, regardless of whether it was clinically indicated. Choosing Wisely (CW) Canada recommends using validated clinical decision support to determine whether a CT scan is necessary for patients presenting with a mTBI. In order to provide patients with information on the risks and benefits of CT scans in mTBI and to encourage discussions between patients and their doctor, the Emergency StrategicClinical Network (ESCN) designed a patient focused information visualization on CT scans for head injuries.Methods: The ESCN, Physician Learning Program and CW Alberta partnered with the Mount Royal University Department of Information Design to develop a patient information visualization (infographic) intervention. Students spent a semester developing these infographics on Choosing Wisely recommendations, which were then presented to stakeholders. A student was then selected to develop a final design. Refinement of the design took place in consultation with clinical experts and tested in two patient focus groups. The final design was evaluated against the International Patient Decision Aid Standards checklist. The infographic was posted in 2 local emergency department waiting rooms. A survey was administered to any patients in the waiting room when volunteers were available. The survey was designed to evaluate whether the tool influenced patient beliefs about the risks and benefits of CT scans, and their willingness to engage in a discussion with their doctor.Results: In a 26 day period, 90 patients consented and completed the survey. Before reading the infographic, 33% of patients thought that after a head injury a CT was always a good idea and 63% thought it was sometimes a good idea. 82% and 91% of patients stated the poster helped them understand the indications and risks of CT imaging for mTBI. After viewing the poster, only 15% of patients felt that a CT was always a good idea after a mTBI.Conclusion: The mTBI patient infographic significantly changed patient perceptions regarding the need for CT scans in the setting of mTBI. This study demonstrates that targeted patient education materials can help support CW recommendations.